Assessment of a novel aminated magnetic adsorbent with excellent adsorption capacity for dyes and drugs. (1st September 2021) - Chen, Wei; Liu, Zhujun; Tang, Qian; Du, Bin; Huang, Xianbin; Mo, You; Fan, Liangqian; Luo, Hongbing; Chen, Fenghui
Abstract: Dyes and drugs with high toxicity and low biodegradability pose risk to human health and ecological security, and should be purified efficiently from effluents before discharge. Traditional adsorbents are limited by the insufficient active adsorption sites and low stability. In this study, a novel aminated magnetic adsorbent (MCTs) was fabricated via two cross-linking steps using chitosan and triethylenetetramine to fill the gaps between current adsorbent and performance requirements. The morphological and physicochemical characteristics of the as-prepared MCTs were determined and identified with the aid of several characterization techniques. The adsorption performance of dyes and drugs was also investigated and represented by their adsorption capacities. In particular, the adsorption capacities of Congo Red, Chicago Sky Blue, Reactive Brilliant Red, and Ibuprofen were 583.11, 465.01, 403.12, and 291.71 mg/g, respectively. They also remained at around 80% after four reuse cycles. MCTs were adsorbed via a monolayer spontaneous chemical reaction, and hydrogen bonding and electrostatic interaction were the dominant adsorption mechanisms. These results demonstrated that the preparation of MCTs via two cross-linking steps enhanced the adsorbents' adsorption capacity, reusability, and stability. They provided a new perspective for the preparation of high-efficient adsorbents and the purification of dye- and drug-polluted wastewater. Graphical abstract: Image 1 Highlights: Novel aminated magnetic adsorbent MCTs was fabricated by two cross-linking step. The maximum adsorption capacity of MCTs for Congo Red is 583.11 mg/g. MCTs performed higher stability in extreme acid solution. Chelation, hydrogen bonding and electrostatic effect contributed to adsorption.